The impact of the COVID‐19 pandemic on the diagnosis of cutaneous melanomas: A retrospective cohort study from five European skin cancer reference centres. (3rd March 2023) - Troesch, Alexander; Hoellwerth, Magdalena; Forchhammer, Stephan; Del Regno, Laura; Lodde, Georg; Turko, Patrick; Cheng, Phil F.; Levesque, Mitchell L.; Hadaschik, Eva; Livingstone, Elisabeth; Peris, Ketty; Flatz, Lukas; et al.
Abstract: Background: The COVID‐19 lockdown had a dramatic impact on primary care access and resulted in postponed skin cancer screenings. This raises concerns for a diagnostic delay on primary cutaneous melanomas, which can subsequently increase morbidity and mortality. Objectives: The aim of the study was to investigate the impact of the COVID‐19‐related restrictions on the melanoma diagnosis in five European skin cancer reference centres in Switzerland, Germany, Austria and Italy. Methods: A total of 7865 cutaneous melanoma cases were collected between 01 September 2018 and 31 August 2021. The time period was stratified into pre‐COVID (pre‐lockdown) and post‐COVID (lockdown and post‐lockdown) according to the established restrictions in each country. The data collection included demographic, clinical and histopathological data from histologically confirmed cutaneous melanomas. Personal and family history of melanoma, and presence of immunosuppression were used to assess the diagnosis delay in high‐risk individuals. Results: There was an overall increase of the Breslow tumour thickness (mean 1.25 mm vs. 1.02 mm) during the post‐COVID period, as well as an increase in the proportion of T3‐T4 melanomas, rates of ulceration and the number of mitotic rates ≥2 (all, p < 0.001). Patients with immunosuppression and personal history of melanoma showed a decrease in the mean log10‐transformed Breslow during lockdown and post‐COVID. In the multivariate analysis, age at melanoma diagnosis ( p < 0.01) and personal history of melanoma ( p < 0.01) showed significant differences in the mean Breslow thickness. Conclusions: The study confirms the diagnostic delay in cutaneous melanomas due to the COVID‐19 lockdown. High‐risk individuals, such as patients with personal history of melanoma and elderly individuals, were more hesitant to restart their regular skin cancer screenings post‐COVID. Further studies with longer follow‐up are required to evaluate the consequences of this diagnostic delay in long‐term outcomes.